Factor H binding protein (fHbp)-mediated differential complement resistance of a serogroup C Neisseria meningitidis isolate from cerebrospinal fluid of a patient with invasive meningococcal disease - Facchetti, A; Wheeler, JX; Vipond, C; Whiting, G; Lavender, H; Feavers, IM; Maiden, MCJ; Maharjan, S (Microbiology Society, 2021)
During an outbreak of invasive meningococcal disease (IMD) at the University of Southampton, UK, in 1997, two Neisseria meningitidis serogroup C isolates were retrieved from a student (‘Case’), who died of IMD, and a close contact (‘Carrier’) who, after mouth-to-mouth resuscitation on the deceased, did not contract the disease. Genomic comparison of the isolates demonstrated extensive nucleotide sequence identity, with differences identified in eight genes. Here, comparative proteomics was used to measure differential protein expression between the isolates and investigate whether the differences contributed to the clinical outcomes. A total of six proteins were differentially expressed: four proteins (methylcitrate synthase, PrpC; hypothetical integral membrane protein, Imp; fructose-1,6-bisphosphate aldolase, Fba; aldehyde dehydrogenase A, AldA) were upregulated in the Case isolate, while one protein (Type IV pilus-associated protein, PilC2) was downregulated. Peptides for factor H binding protein (fHbp), a major virulence factor and antigenic protein, were only detected in the Case, with a single base deletion (ΔT366) in the Carrier fHbp causing lack of its expression. Expression of fHbp resulted in an increased resistance of the Case isolate to complement-mediated killing in serum. Complementation of fHbp expression in the Carrier increased its serum resistance by approximately 8-fold. Moreover, a higher serum bactericidal antibody titre was seen for the Case isolate when using sera from mice immunized with Bexsero (GlaxoSmithKline), a vaccine containing fHbp as an antigenic component. This study highlights the role of fHbp in the differential complement resistance of the Case and the Carrier isolates. Expression of fHbp in the Case resulted in its increased survival in serum, possibly leading to active proliferation of the bacteria in blood and death of the student through IMD. Moreover, enhanced killing of the Case isolate by sera raised against an fHbp-containing vaccine, Bexsero, underlines the role and importance of fHbp in infection and immunity.